The Effect of Return On Equity (ROE) and Net Profit Margin (NPM) on Stock Prices - Sovi Oktaviani Rahayu; Achmad Agus Yasin Fadli (Indonesian Development of Economics and Administration Journal, 2023)
This study aims, to determine the effect of Return On Equity (ROE) and Net Profit Margin (NPM) together on the Share Price at Pt. BFI Finance Tbk period 2011 - 2022 The research method used in this research is quantitative descriptive research, where in quantitative research researchers generally use measuring instruments for data collection. the research variables used in this study used statistical tests which include classical assumption tests and multiple linear regression. In classical assumptions, the test instruments used by researchers are normality, multicollinearity, heteroscedasticity and autocorrelation tests.  Partially, researchers used the t test, while simultaneously using the F test, which was then continued using the coefficient of determination test. Based on the results of the F test calculation above, it shows F count 4.292> F table 4.10 with a significant level of Return On Equity (ROE) and Net Profit Margin (NPM) to the Share Price at Pt. BFI Finance Tbk so it can be concluded that H0 is rejected and H3 is accepted, which means it has an effect on the Share Price at PT. BFI Finance tbk.